Adaptive assessment course : useful AI tools in higher education / Dr. Leow Min Hui and Dr. Norhaslinda Hassan - Leow, Min Hui; Hassan, Norhaslinda (Academy of Language Studies, 2023)
AI, or Artificial Intelligence, is revolutionising the education landscape by providing personalised learning experiences for students and data-driven insights for educators. Recently, we participated in an interactive two-day workshop titled "Assessment Reimagined: Unravelling the AI Revolution in Higher Education." This interactive workshop offered a deep-dive exploration of integrating AI into teaching and assessment practices. During the workshop, we embarked on an exciting AI journey, discovering the potential of AI to transform and enhance four key assessment strategies: Problem-Based, Project-Based, Inquiry-Based, and Group-Based assessments. The workshop struck a perfect balance between theoretical concepts and practical applications, introducing participants to the world of AI, its potential in teaching and learning, and how it can be practically applied in their assessment practices. The workshop's structure was thoughtfully designed, offering a rich blend of theoretical knowledge sharing, hands-on AI tool exploration, and engaging assessment simulations. This approach kept us thoroughly engaged and empowered us to understand the real impact of AI on various teaching and assessment methods.